PENEGAKAN PELANGGARAN MORAL DAN ETIK PENYELENGGARAAN PEMILU DI INDONESIA : ANALISIS KONSTRUKSI DAN IMPLEMENTASINYA (Jurnal De Jure Muhammadiyah Cirebon, 2025)
This study aims to analyze in depth the construction and implementation of moral and ethical violation enforcement in the implementation of General Elections (Pemilu) in Indonesia. This study uses a qualitative approach with a case study design. Data were collected through analysis of legal documents and regulations related to the enforcement of Election ethics (Laws, KPU Regulations, DKPP Code of Ethics), in-depth interviews with members of the Election Organizer Honorary Council (DKPP), KPU and Bawaslu commissioners, Election law scholars, and democracy practitioners and activists. In addition, participatory observation of DKPP decisions related to ethical violations was also conducted to understand the pattern and consistency of enforcement. The results of the study indicate that the construction of laws and regulations related to the enforcement of moral and ethical violations of election organizers in Indonesia is quite comprehensive, especially with the existence of DKPP as an institution enforcing the code of ethics.Keywords: Violations, Elections, and the Law